Comparative Immunohistochemical Study of the Distribution of CK 8/18 and CK-Cocktail in the Liver Epithelium of Three Vertebrate Species - Mzik, Heba; Ebrahim, Nahla; Ismail, Saleh (International Journal of Scientific Research in Biological Sciences, 2020)
The purpose of this study, is to perform immunohistochemical comparison of the liver epithelium in three vertebrate species: Hyla savignyi, Hemidactylus turcicus and Testudo graeca, by using the antibodies CK8/18 and CK-cocktail. This assay determines the evolution of animal tissues by investigating the presence of cytokeratin and its density in these tissues. The tissues have shown different expression levels using CK-cocktail antibodies, where the bile ducts gave a strong signal at Hyla savignyi, and the cytoplasm of hepatocytes gave a medium signal. As for Hemidactylus turcicus, the bile ducts gave a medium signal and the cytoplasm of hepatocytes gave a slight signal. However, the bile ducts and the cytoplasm of hepatocytes signals were strong at Testudo graeca, which confirms the existence of cytokeratin in the liver epithelium of the studied species. On the other hand, the tissues have shown CK8/18 -negative signal in Hyla savignyi and Hemidactylus turcicus, in contrast to the tissues of Testudo graeca.